2021
DOI: 10.1016/j.breast.2020.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Residual breast tissue after robot-assisted nipple sparing mastectomy

Abstract: Introduction: While the long-term oncologic safety of robot-assisted nipple sparing mastectomy (RNSM) remains to be elucidated, histologically detected residual breast tissue (RBT) can be a surrogate for oncologically sound mastectomy. The objective of this study is to determine the presence of RBT after RNSM. Methods: Between August 2019eJanuary 2020, we completed 5 cadaveric RNSMs. Full thickness biopsies from the mastectomy skin flap were obtained from predefined locations radially around the mastectomy ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The ET has limitations in terms of negotiating the convex contour of the posterior chest wall and difficulty maintaining an optical window, which leads to operational difficulty, insufficient LDMF volume, and a prolonged operation time ( 3 , 5 ). The RT improves visualization and surgical dexterity but is still not as good as open surgery ( 6 ). Additionally, the RT has the disadvantages of high costs and a doubled docking time caused by changes in the patient’s position ( 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ET has limitations in terms of negotiating the convex contour of the posterior chest wall and difficulty maintaining an optical window, which leads to operational difficulty, insufficient LDMF volume, and a prolonged operation time ( 3 , 5 ). The RT improves visualization and surgical dexterity but is still not as good as open surgery ( 6 ). Additionally, the RT has the disadvantages of high costs and a doubled docking time caused by changes in the patient’s position ( 3 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…To study the technical feasibility and safety of RNSM, we performed a series of cadaveric RNSM and assessed the mastectomy flap for the presence of residual breast tissue. 16 We were able to demonstrate that RNSM is technically feasible. Residual breast tissue was only detectable in the NAC, and none was detectable in the mastectomy flap outside the NAC.…”
Section: Introductionmentioning
confidence: 84%
“…Eligible patients will undergo RNSM as previously described. 16 Briefly, the anterior axillary incision will be used for dissection. The breast incision, measuring approximately 3 cm, will be placed just lateral to the anterior axillary line.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Residual breast tissue (RBT) after mastectomy can contribute to breast cancer recurrence and serve as a surrogate marker for surgical oncological outcomes (Griepsma et al , 2014). Park et al (2021) conducted a study on RBT after RNSM and reported that RNSM was feasible, leaving minimal RBT in the mastectomy flap. Although additional large-scale studies are needed on RBT after RNSM, minimal RBT is considered indirect evidence of the promising long-term oncologic safety of RNSM.…”
Section: Strengthsmentioning
confidence: 99%